Asymmetric Supercapacitors: Covalent Graphene‐MOF Hybrids for High‐Performance Asymmetric Supercapacitors (Adv. Mater. 4/2021). Issue 4 (25th January 2021) - Jayaramulu, Kolleboyina; Horn, Michael; Schneemann, Andreas; Saini, Haneesh; Bakandritsos, Aristides; Ranc, Vaclav; Petr, Martin; Stavila, Vitalie; Narayana, Chandrabhas; Scheibe, Błażej; Kment, Štěpán; Otyepka, Michal; et al.
Abstract : In article number 2004560, Kolleboyina Jayaramulu, Deepak Dubal, Radek Zboril, Roland A. Fischer, and co‐workers report covalent attachment of graphene acid (GA) and an amine‐functionalized metal–organic framework (UiO‐66‐NH2 ) via the amide bond. The hybrid GA@UiO‐66‐NH2 acts as an effective charge‐storing material with a remarkable capacitance. They construct an asymmetric supercapacitor (ASC) using GA@UiO‐66‐NH2 as the positive electrode, with Ti3 C2 T x MXene as negative electrode.